Structure and energetics of cyclopropane carboxaldehyde. Issue 8 (5th June 2012) - Trindle, Carl; Bleda, Erdi A.; Altun, Zikri
Abstract We use the energies obtained by a focal point analysis including extrapolation from results with basis sets cc‐pVnZ and aug‐cc‐pVnZ with n up to 4 and correlation corrections through CCSD(T), to estimate thermodynamic functions for the syn and anti isomers of cyclopropane carboxaldehyde (CPCA). These agree with values obtained by well‐established thermochemical schemes CBS‐QB3 and G4. The structures obtained in these studies also conform to the best experimental determination of the rotational constants in the gas phase. The kinetics of gas phase interconversion of the syn‐ and anti‐isomers of CPCA have been studied by a chirped‐pulse dynamic rotational spectroscopy. Computational modeling of the internal rotational potential allows the estimate of the interconversion rates by statistical (RRKM) methods. RRKM rates using a range of barrier heights including a CBS‐Q estimate are more than 10× the rates deduced from the dynamical rotational spectra. This suggests that nonstatistical effects may be limiting the rate. Detailed study of the interconversion potential by a variant of the focal point analysis suggests that previous estimates of the barrier may be too low, and thus, the inferred rice‐ramsperger‐kassel‐marcus (RRKM) rate could be too high. These results cast some doubt on the presence of nonstatistical effects and suggest that molecular dynamics studies should be conducted to characterize the energy flow in detail. © 2013 Wiley Periodicals, Inc.